Recent Advances of Aqueous Rechargeable Zinc‐Iodine Batteries: Challenges, Solutions, and Prospects. Issue 23 (3rd April 2022) - Lin, Dun; Li, Yat
Abstract: Aqueous rechargeable zinc‐iodine batteries (ZIBs), including zinc‐iodine redox flow batteries and static ZIBs, are promising candidates for future grid‐scale electrochemical energy storage. They are safe with great theoretical capacity, high energy, and power density. Nevertheless, to make aqueous rechargeable ZIBs practically feasible, there are quite a few hurdles that need to be overcome, including self‐discharge, sluggish kinetics, low energy density, and instability of Zn metal anodes. This article first reviews the electrochemistry in aqueous rechargeable ZIBs, including the flow and static battery configurations and their electrode reactions. Then the authors discuss the fundamental questions of ZIBs and highlight the key strategies and recent accomplishments in tackling the challenges. Last, they share their thoughts on the future research development in aqueous rechargeable ZIBs. Abstract : Aqueous rechargeable zinc‐iodine batteries (ZIBs), including zinc‐iodine redox flow batteries and static ZIBs, are promising candidates for future grid‐scale electrochemical energy storage. This article reviews the electrochemistry in ZIBs, discusses their fundamental questions, and highlights the key strategies and recent accomplishments in tackling the challenges. This review also provides perspectives on the future research development of ZIBs.